ALAT BANTU BERJALAN BAGI LANSIA YANG MENGALAMI GANGGUAN PENGLIHATAN UNTUK MEMINIMALKAN RISIKO JATUH - Moh Dzakiy Naashiruddiin; Rika Maya Sari; Sri Andayani (Universitas Muhammadiyah Ponorogo, 2022)
The risk of falling in the elderly can be influenced by changes due to the aging process and an unsafe environment. One of the changes in cognitive function resulting in a decline. The purpose of this study was to carry out nursing care actions for elderly people with visual impairments with nursing problems at risk of falling. Nursing care for the elderly with visual impairments with nursing problems at risk of falling was carried out at the Tresna Werdha Panti Social Unit, Magetan Regency for 6 days from 09 June to 14 June 2022. The research method used was the nursing process including assessment, intervention, implementation and evaluation of nursing. The results of the study found that Mr. J has visual impairment which gets a score of 13 so he is included in a high risk condition for falling. Nursing action taken is fall prevention. It can be concluded, after taking nursing actions the problem of falling risk is partially resolved. The client is able to maintain the balance of the stick, the client is able to overcome vision problems by using an umbrella when leaving the room so as not to be dazzled by the sun. The client can explain again how to prevent the risk of falling that has been taught by the researcher. The research results achieved are in accordance with theory and facts, so there is no gap between theory and results.Keywords : Elderly, Visual Impairment, Fall Risk